Prejudice and Ethnic Bullying Among Children: The Role of Moral Disengagement and Student-Teacher Relationship - Iannello, Nicolò Maria; Camodeca, Marina; Gelati, Carmen; Papotti, Noemi (Frontiers in Psychology, 2021)
The identification of factors associated with ethnic bullying within multiethnic schools is a timely social issue. Up to now, ethnic prejudice has been found to facilitate aggression triggered by schoolmates’ cultural background. Yet, there is still a dearth of research about the mechanisms underlying this relation among children. In order to fill this gap, by adopting a social-cognitive developmental perspective on prejudice and morality, this paper investigated the mediating role of moral disengagement in the association between ethnic prejudice and ethnic bullying, as well as the moderating role of closeness with the teacher. A mediation model and a moderated mediation model were applied to data collected from 552 primary school children aged 8-10 years. Ethnic prejudice, ethnic bullying, and moral disengagement were assessed through self-reported questionnaires, whereas a questionnaire was administered to teachers to assess the level of closeness with their pupils. Results indicated that ethnic prejudice was directly and positively related to ethnic bullying and that moral disengagement partially mediated this association. This indirect link was particularly strong for children with low levels of closeness with their teachers, whereas it resulted not significant for pupils with high levels of closeness, suggesting that closeness with the teacher might restrain morally disengaged children from enacting ethnic bullying. Implications for research and practice aimed at reducing prejudice and moral disengagement, as well as at promoting positive relationships among children and between pupils and teachers, are discussed.